TEACHERS’ AND STUDENTS’ ATTITUDES TOWARD THE IMPLEMENTATION OF PROJECT-BASED LEARNING - Mesakh Tamu Ama (Adisam Publisher, 2026)
Project-based learning (PBL) has been around for decades and in Indonesia, this learning model has been prominently used since the COVID-19 pandemic in an effort to address potential learning loss through the curriculum known as the Emergency Curriculum. This study aims to discuss the main benefits and challenges students face and the changes that could be made to improve the overall potential of PBL. In this research, descriptive qualitative design was used to provide a comprehensive outlook on respondents’ views on PBL implementation in class. This research used heterogeneous purposive sampling methods when selecting respondents and involved thirty students and ten experienced teachers. The results suggest that PBL provides an immersive and more hands-on learning experience and it is believed that it is crucial in helping students improve their understanding of a subject matter and develop critical skills. Respondents also identify some key challenges that they still face in class including unequal student participation in groups, lack of clear communication, and differences of opinion. For a better implementation of PBL in class, respondents believe that a few things need to be done, including better grouping practices, providing clear instructions, and providing constructive feedback and progress monitoring during a project.